Tear Resistance of Laminated and Non-laminated Paperboard Types Ivory and Duplex in Packaging Materials - Ardiani, Septia; Suryani, Meuthia; Akmalia, Nurul (KnE Engineering, 2024)
A paperboard is a packaging material that has the disadvantage of being easily torn. One of the techniques used to overcome this is lamination. Two types of paperboard are often used as packaging materials, namely duplex and ivory. This research aimed to analyze the tear resistance comparison between duplex and ivory paperboard types. There are four types of samples in this research, namely duplex non-lamination, duplex lamination, ivory non-lamination, and ivory lamination. The variations of duplex and ivory grammation used include 350 gsm, 300 gsm, 270 gsm, 250 gsm, 230 gsm, and 210 gsm. Measurement of tear resistance refers to SNI 1974:2012 using the Elmendorf method. Each sample was measured for the CD and MD directions. The results showed that for the same grammage, the tear resistance of ivory was greater than that of duplex. The highest increase in tear resistance occurred in duplex and ivory with grammatical 210 gsm. The percentage increase in tear resistance of duplex and ivory with grams of 210 gsm, 230 gsm, 250 gsm is more than 20%, while for higher grams the percentage is less than 15%. The higher the grammage, the lower the percentage increase in tear resistance. Keywords: paperboard, duplex, ivory, tear resistance